The Android-based Student Progress Notifier Application at Universitas Klabat - Green Ferry Mandias, S.Kom, M.Cs; Devid Runtuwene (CogITo Smart Journal, 2019)
In the world of education, it was found that there were students who had problems in terms of motivation and enthusiasm that were lacking in learning. Likewise the expectations of students get a high score, but get a less grade at the end of the semester. Of course there is a need to monitor the progress or achievement of each student. In this study the author uses Web service and Android technology which aims to build mobile applications with the Android platform, which can serve to help students monitor academic development. The development method used in this study is prototyping, which is a model process that makes the output of development a prototype. From the teacher's side the researchers used a Web platform using the Code Igniter framework with the Maria DB database. The programming language used in the study consists of php to handle from the teacher side, Java to handle the logic of the program from the student side. The tools used in this study are Android studio for handling Android applications, Sublime Text as a text editor to make it easier for writers to write programs, Emulator Genymotion as a virtual machine to conduct initial tests of Android applications, Mozilla Firefox for testing Web Applications. This research produces Android and Web applications that can assist students in monitoring learning progress, and lecturers or teachers in informing grades in class.